Isolated Pheochromocytoma in a 73-Year-Old Man With No Clinical Manifestations of Type 1 Neurofibromatosis Carrying an Unsuspected Deletion of the Entire NF1 Gene - Parisien-La Salle, Stefanie; Dumas, Nadine; Rondeau, Geneviève; Latour, Mathieu; Bourdeau, Isabelle (Frontiers in Endocrinology, 2019)
Pheochromocytomas (PHEOs) are a rare cause of endocrine hypertension that requires genetic counseling since at least 30% of PHEOs are associated with a germline mutation in a susceptibility gene. Neurofibromatosis type 1, NF1 is amongst the 16 known causing genes for pheochromocytomas/paragangliomas. We report a case of a 73-year-old man with PHEO in whom genetic testing revealed a large pathogenic heterozygous deletion of 1.14 Mb encompassing the entire coding sequence of the NF1 gene while the patient showed no signs of clinical NF1.This case illustrates that the diagnosis of NF1 should not be excluded in patients with PHEO in the absence of clinical diagnosis of the disease and support that older patients with PHEO should also be offered genetic counseling.